L’émergence d’une forme de nanopunk au Japon : Gunnm (Ganmu 銃夢) de Kishiro Yukito - Denis Taillandier (ReS Futurae)
Focusing on the manga Battle Angel Alita (Ganmu) by Kishiro Yukito (1991-95), this paper examines how Japanese science fiction rapidly integrated the most representative elements of the nanotechnological imagination. Ganmu is one of the first works of science-fiction in Japan to introduce the nanomachines envisioned by Eric Drexler (1986) and to provide at the same time a critical illustration of the dream of total control over matter. Following a brief outline on the close connections that link nanotechnology to science-fiction, it presents the technical notes the mangaka inserted in his work to provide a background on nanotechnology which forms the basis of Kishiro’s take on human enhancement. Building on semiotics and the Greimas square to unravel the symbolic structure of the manga, it shows that Ganmu is articulated around two polarities : between natural and artefactual on the one hand, and between matter and mind on the other. The manga thus raises an essential question, that of the definition of what is human in a world reshaped by technosciences. Inspired by an ethics of perfectibility, Kishiro attempts at answering it by defining humanness not so much by physiology, nor by self-consciousness, but rather by will and emotions, actions and the responsibility that comes with them. Although the conclusion of the first series seems to come back to a status quo the figure of the cyborg aimed at overcoming, the almost similar ending of the second series, Battle Angel Alita : Last Order (Ganmu LastOrder) eventually opens new perspectives in terms of relationships between humans and non-humans.